Intensive training induces longitudinal changes in meditation state-related EEG oscillatory activity - Saggar, Manish; King, Brandon G.; Zanesco, Anthony P.; MacLean, Katherine A.; Aichele, Stephen R.; Jacobs, Tonya L.; Bridwell, David A.; Shaver, Phillip R.; Rosenberg, Erika L.; Sahdra, Baljinder K.; Ferrer, Emilio; Tang, Akaysha C.; et al. (Frontiers in Human Neuroscience, 2012)
The capacity to focus one’s attention for an extended period of time can be increased through training in contemplative practices. However, the cognitive processes engaged during meditation that support trait changes in cognition are not well characterized. We conducted a longitudinal wait-list controlled study of intensive meditation training. Retreat participants practiced focused attention meditation techniques for three months during an initial retreat. Wait-list participants later undertook formally identical training during a second retreat. Dense-array scalp-recorded electroencephalogram (EEG) data were collected during six minutes of mindfulness of breathing meditation at three assessment points during each retreat. Second-order blind source separation, along with a novel semi-automatic artifact removal tool, was used for data preprocessing. We observed replicable reductions in meditative state-related beta-band power bilaterally over anteriocentral and posterior scalp regions. In addition, individual alpha frequency decreased across both retreats and in direct relation to the amount of meditative practice. These findings provide evidence for replicable longitudinal changes in brain oscillatory activity during meditation and increase our understanding of the cortical processes engaged during meditation that may support long-term improvements in cognition.